PTB 59 -‘Samyuktha’ a high yielding rice variety for kootumundakan system of cultivation in Kerala - Francies, Rose Mary; Joseph, Jiji; Zacchariah, Gregory; Leenakumary, S; Raji, P; Karthikeyan, S; Sudarsana Rao, G.V (Journal of Tropical Agriculture, 2013)
PTB 59 ‘Samyuktha’ specifically bred for koottumundakan system of cultivation in Kerala, is a pureline, selected from Culture C3-2 developed through hybridization and selection, with M 210 (the dwarf mutant of traditional tall indica rice variety PTB 10) and PTB 28 as parents. Samyuktha is a photo-period insensitive, medium tillering variety of 112 – 117 days duration, growing to an average height of 123 cm with a yield potential of 3600 kg ha-1 under koottumundakan system. This short-bold red kernelled rice variety is moderately resistant to major pests of rice crop. It is non-lodging in the koottumundakan system of cultivation, with non-shattering grains and moderate dormancy. Considering its qualities, PTB 59 ‘Samyuktha’ was released as a variety for cultivation in koottumundakan system during 2010 .